Optic Neuritis - Mahmood, Tahir (Pakistan Journal of Ophthalmology, 2008)
Optic neuritis is a term used to refer to inflammation of the optic nerve. When it is associated with a swollen optic disc, it is called papillitis or anterior optic neuritis. When the optic disc appears normal, the terms retrobulbar optic neuritis or retrobulbar neuritis are used. Acute optic neuritis is by far the most common type of optic neuritis that occurs throughout the world and is the most frequent cause of optic nerve dysfunction in young adults. The annual incidence of acute optic neuritis is estimated in population-based studies to be between 1 and 5 per 100,000 1. The majority of patients with acute optic neuritis are between the ages of 20 and 50 years, with a mean age of 30 to 35 years; however, optic neuritis can occur at any age. Females are affected more commonly than males by a ratio of approximately 3:12.